THE EFFECT OF TEACHING WITHIN-TEXT KEY WORDS ON STUDENTS’ PERFORMANCE IN READING COMPREHENSION - Khodasenas, Mohammad Reza (Indonesian Journal of Applied Linguistics, 2013)
Abstract: The present study was conducted to investigate the effects of teaching within-text key word synonyms, opposites and related words on students’ performance on reading comprehension of TOEFL among Iranian EFL learners. To carry out the research, 60 Iranian EFL learners, who participated in a TOEFL preparation course, were selected as the participants of the study. Afterward they were randomly assigned into experimental and comparison groups. The experimental group was given a treatment including within-text key word synonyms, opposites and their translations, while the comparison group was given a placebo. To collect the required data, two instruments (a pre-test, and a post-test) were administered to both groups during the experimentation. Subsequently, students’ scores were collected through the administration of different tests and the results were statistically analyzed. The results of these analyses revealed that the experimental group outperformed the comparison group and thus, it was concluded that teaching within-text key word synonyms, opposites and related words can improve the reading comprehension ability and general proficiency of EFL language learners.